To what Extent the Social Safety Net (JPS) Implement in Sleman Regency - Rahmat, Al Fauzi; Pujiartini, Pujiartini; Purwaningsih, Titin (Jurnal Transformative, 2020)
To strengthen social security for people with social welfare issues, the Sleman Regency government has implemented a Social Security Net (JSP) policy. Nevertheless, its management often poses obstacles and challenges in line with the implementation. This article aims to examine the implementation of the Social Safety Net (JPS) policy in Sleman regency, as a cash assistance program that has a significant influence on the basic needs of people's lives in the health, education and social sectors. Furthermore, this research method uses a qualitative approach with data collection techniques through in-depth interviews and performance reports. The results of this study are the Sleman Regency government through the Department of Social Service as an extension of the government sector that manages the JPS program still has a lack of personnel resources to handle the verification process and data validity of the JPS recipient. Nevertheless, the JPS program has a strong network of actors to work with the Regional Development Planning Agency, the Regional Finance and Assets Agency, the Department of Health, and social workers at the sub-district and village levels. However, a critical review of this implementation is that there is no solution to the problems of life for the people who receive funding from JPS. Programs provided by the government seem to be able to prevent and deal with risks from social shocks and vulnerabilities, but there is no government effort to design the program, which provides change for people who have social vulnerabilities. In this context, it certainly gives them life dependence because this program is only as unplanned social assistance in the form of money given to them.